Representations of Fear in Gothic Novel - Douda, Filip (Univerzita Pardubice, 2023)
The bachelor thesis depicts the representation of fear in Gothic Novel in two literary sources; R. L. Stevenson's Strange Case of Dr Jekyll and Mr Hyde and Mary Shelley's Frankenstein. To understand how fear functions and is depicted in these literary sources, the theoretical part provides brief historical development of Gothic Novel, cultural and social background of the late Gothic Novel. The following part is based on the analysis of elements of fear in the two selected works.
Vyobrazení strachu v gotickém románu
Keywords: Podivný případ doktora Jekylla a pana Hyda; Frankenstein; strach; gotický román; viktoriánské období; Strange Case of Dr Jekyll and Mr Hyde; Frankenstein; fear; gothic novel; Victorian era